UPAYA SEKOLAH DALAM MENANGGULANGI KENAKALAN SISWA (STUDI KASUS SISWA DI SMA “Z” PEKANBARU) - Munir , Abdul; Naufal Rizqy , Muhammad (UIR PRESS, 2021)
Juvenile delinquency is adolescents transition results which makes adolescents which is often associated with students. where at a time like this often emotional or psychological instability. in this transition adolescence are looking for identity. but often searching for identity adolescents or students tend to be wrong in socializing so many do things that deviate from the norms that exist in society. that's what makes adolescents or students often do deviant behavior called juvenile delinquency. juvenile delinquency is various kinds of adolescent behavior that is not socially acceptable so that criminal acts occur. Schools are one of the places where juvenile delinquency prevention efforts are carried out by students. Results of this study is all forms of SMA Z efforts in Pekanbaru to tackle student delinquency. this type of study are the qualitative which aims to describe the original situation that occurred at the research location through observation, analysis, and interviews in order to obtain answers to the problems that have been formulated. so this study concludes that the school is aware of the existence of delinquency committed by students, then make efforts to prevent and impose sanctions on students in order to have a deterrent effect and hopefully not repeating his delinquency again.